1991
DOI: 10.1177/103841119102900105
|View full text |Cite
|
Sign up to set email alerts
|

Annual Review Paper : Occupational Health and Safety: Progress and Problems

Abstract: Occupational health and safety has continued to gain recognition as an important issue for managers and workers in Australia. Significant progress has been made in recent years, particularly with regard to occupational health and safety legislation. While some problems in the workplace have been addressed, several issues have emerged as problems requiring attention in the 1990s. Current trends are moving away from a compensatory approach, towards the prevention of hazardous workplace conditions and practices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There is no doubt that organizations should take preventative measures and that top management support is needed to achieve this (Schuler et al, 1992: 398-9;Stone, 1991: 399-401;DeCieri, 1991;French, 1990: 648). To achieve this end, effective prevention strategies need to be implemented; however, these must be financed in the first place.…”
Section: Occupational Health and Safety In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no doubt that organizations should take preventative measures and that top management support is needed to achieve this (Schuler et al, 1992: 398-9;Stone, 1991: 399-401;DeCieri, 1991;French, 1990: 648). To achieve this end, effective prevention strategies need to be implemented; however, these must be financed in the first place.…”
Section: Occupational Health and Safety In Organizationsmentioning
confidence: 99%
“…Managers therefore should be convinced of the need for, and value in, outlaying time and money on prevention. There is no doubt that organizations should take preventative measures and that top management support is needed to achieve this (Schuler et al, 1992: 398-9;Stone, 1991: 399-401;DeCieri, 1991;French, 1990: 648). One of the chief barriers to managers releasing the purse-strings is their lack of understanding for the need for OHS initiatives-in one recent report (Ruzek, 1990), it was found that about 80% of managers had no training in OHS.…”
Section: Occupational Health and Safety In Organizationsmentioning
confidence: 99%